Federal Participation in the Costs of Housing — a “Pragmatic” Transfer - Florian Boettcher; Ronny Freier; René Geißler (Wirtschaftsdienst)
Abstract Since the introduction of SGB II in 2005, the federal government cofunded costs of housing aiming to reduce the financial burden of local authorities. Over the years, the amount, structure, calculation and purpose of this federal contribution were constantly changing. This article looks at how this transfer evolved over time, the components that it consists of today, and the debates that came up. Based on this analysis, the authors conclude that the federal contribution should be simplified by phasing out regional privileges and by financing different benefits in different ways.